Analisis Filogenetik Lebah Tukang Kayu Xylocopa appendiculata Smith, 1852 Berdasarkan Gen Cytochrome Oxidase 1 (CO1) - Rahayu, Irma Septi; Budiarsa, I Made; Ashari, Abdul; Trianto, Manap; Masrianih, Masrianih; Rafiqa, Rafiqa (Bioscientist : Jurnal Ilmiah Biologi, 2025)
Xylocopa appendiculata Â is an insect from the order Hymenotera and has bright yellow morphological characteristics on the thorax, while the rest of the body is black. Phylogenetic analysis is used to describe the kinship of living things throughh phylogeny trees. This study aims to describe the phylogenetic relationship of carpenter bees Xylocopa appendiculata based on the cytochrome oxidase 1 (CO1). DNA isolation, DNA amplification, sequencing, followed by bioinformatics analysis using GeneStudio, DNASTAR, MESQUITE, and MEGA 11. The results showed that phylogenetic analysis using Neighbor-Joining (NJ) and Maximum Likelihood (ML) methods produced a phylogenetic tree that illustrates a clear evalutionary relationship X. appendiculata from Central Sulawesi is more closely related to other X. appendiculata species in the same clade. The results of this study show a clear kinship pattern between populations of X. Appendiculata.